Constraints on Pore Development in Marine Shales of the Upper Yangtze Area, South China: A Comparative Case of Lower Cambrian and Lower Silurian Formations - Miao, Yanan; Zhang, Fan; Wang, Shuai; Wu, Fan; Li, Xin (Frontiers in Earth Science, 2022)
Both Lower Cambrian and Lower Silurian shale are typical of oil-prone kerogen and siliceous composition, but differ in thermal maturities with 3.56% Ro and 2.31% Ro, respectively. In this paper, pore characteristics were explored between these two shales. All samples were studied by a combination of organic geochemistry, x-ray diffraction, N2 adsorption, helium porosity, and focused ion beam milling and scanning electron microscopy. In particular, N2 adsorption of isolated OM was conducted to compare physical properties of OM-hosted pores, and fractal dimension was exploited to analyze morphologic characteristics of pores. N2 adsorption indicated that the Lower Silurian shale presented superior pore characteristics than the Lower Cambrian shale, in terms of pore volume (PV), pore surface area (PSA), and pore diameter. FIB-SEM manifested that pinhole OM-hosted pores and open-ended dissolved pores were primarily in the Lower Cambrian shale, while cellular OM-hosted pores were dominant in the Lower Silurian shale. Statistical and fractal analysis demonstrated that OM, rather than minerals, played a dominant role in pore development in marine shales at late diagenetic or metamorphic epoch. Furthermore, OM-hosted pores were not increased monotonously with increasing thermal maturity, but presented a unimodal trend, peaking at 2.8% Ro. PV (PSA) of isolated OM in the Lower Silurian shale was approximately 6.6 (4.3) times higher than that in the Lower Cambrian shale. With similar matrix basics and distinctive pore features, a comparison of these two marine shales markedly emphasizes the impact of thermal maturity on the state of OM-hosted pores.